2003
DOI: 10.1074/jbc.m206383200
|View full text |Cite|
|
Sign up to set email alerts
|

Signaling through P2X7 Receptor in Human T Cells Involves p56 , MAP Kinases, and Transcription Factors AP-1 and NF-κB

Abstract: ATP-gated ion channel P2X receptors are expressed on the surface of most immune cells and can trigger multiple cellular responses, such as membrane permeabilization, cytokine production, and cell proliferation or apoptosis. Despite broad distribution and pleiotropic activities, signaling pathways downstream of these ionotropic receptors are still poorly understood. Here, we describe intracellular signaling events in Jurkat cells treated with millimolar concentrations of extracellular ATP. Within minutes, ATP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 73 publications
(106 reference statements)
4
79
1
1
Order By: Relevance
“…In addition, we have demonstrated that stimulation with extracellular ATP mediates activation of p56 lck , ERK1/2, and JNK in Jurkat T cells [77].…”
Section: Intracellular Signalingmentioning
confidence: 81%
“…In addition, we have demonstrated that stimulation with extracellular ATP mediates activation of p56 lck , ERK1/2, and JNK in Jurkat T cells [77].…”
Section: Intracellular Signalingmentioning
confidence: 81%
“…Stimulation of Jurkat T cells with P2X 7 agonists induces the activation of the lymphoidspecific cytoplasmic protein tyrosine kinase p56 lck [84]. Although the activation of cFos and c-Jun by P2X 7 ligands occurs in Jurkat T cells, it is absent in a p56…”
Section: P2x 7 -Mediated Transcription Factor Activationmentioning
confidence: 99%
“…Furthermore, co-treatment of human fetal astrocytes with IL-1β and ATP was seen to induce an activation of AP-1 that is more robust than that observed with IL-1β alone [93], and treatment with P2 receptor antagonists inhibits cytokine-induced AP-1 activation [93,94]. It has been suggested that stimulation of Jurkat T cells induces AP-1 DNA-binding activity that results from increased c-Jun and cFos expression [84]. Conversely, in the present report, we show that stimulation of human PBMCs with P2X 7 agonists does not appear to enhance cFos expression (Fig.…”
Section: P2x 7 -Mediated Transcription Factor Activationmentioning
confidence: 99%
See 2 more Smart Citations